1997
DOI: 10.1002/(sici)1097-4601(1997)29:4<261::aid-kin4>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of corrosion and dissolution of uranium dioxide as a function of pH

Abstract: A continuous flow-through reactor with a thin layer of solid particles (size ranging from 100 to 300 m) was used to obtain a deeper knowledge on the mechanism of dissolution of UO 2 under oxidizing conditions. Using this methodology the dissolution rate of uranium dioxide was determined at three different oxygen partial pressures (5, 21, and 100% in nitrogen) and as a function of pH (between 3 and 12) in a noncomplexing medium.From the results of these experiments the following rate equation was derived:In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 11 publications
1
27
3
Order By: Relevance
“…Gimenez et al (2005) concluded in their study that the non-stoichiometry was not due to deposition of a secondary solid phase. Torrero et al (1997) determined an average solid surface stoichiometry of UO 2.25 at pH 8.2 as opposed to UO 2.0 at pH 5 and explained this difference by a diminishing rate of proton-promoted dissolution with increasing pH, enabling the incorporation of O 2À species into the UO 2 lattice. Thus, in the absence of more soluble aqueous U-carbonate species at neutral and alkaline conditions, the oxidative dissolution of UO 2+x will be controlled by the detachment of U(VI) and U(V) from the UO 2+x surface.…”
Section: Oxidizing Conditionsmentioning
confidence: 99%
“…Gimenez et al (2005) concluded in their study that the non-stoichiometry was not due to deposition of a secondary solid phase. Torrero et al (1997) determined an average solid surface stoichiometry of UO 2.25 at pH 8.2 as opposed to UO 2.0 at pH 5 and explained this difference by a diminishing rate of proton-promoted dissolution with increasing pH, enabling the incorporation of O 2À species into the UO 2 lattice. Thus, in the absence of more soluble aqueous U-carbonate species at neutral and alkaline conditions, the oxidative dissolution of UO 2+x will be controlled by the detachment of U(VI) and U(V) from the UO 2+x surface.…”
Section: Oxidizing Conditionsmentioning
confidence: 99%
“…4), the composition of the surface of the solid is near UO 2.3 , determined from the deconvolution of the U 4 f(7/2) peak [18]. This composition was also found in UO 2 dissoBrought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/29/15 2:40 PM lution experiments in the presence of oxidants at alkaline pH [19,20] and corresponds to the maximum degree of oxidation observed in electrochemical experiments [21].…”
Section: Resultsmentioning
confidence: 67%
“…At acidic pH the U(VI) formed would dissolve rapidly, while at more alkaline pH, the U(VI) would remain on the surface, as has been also observed for UO 2 oxidation/dissolution by other oxidants [20]. The formation of oxidizing species in solution resulting from β irradiation was studied with the MAK-SIMA code [22] by using the radiolytical model developed by Quiñones et al [5] and the effective G values from Kelm et al [23] that are given in Table 2.…”
Section: Resultsmentioning
confidence: 67%
“…Uraninite dissolution kinetics was taken from Torrero et al (1997): This law established for a synthetic uraninite and for a pH in the range of 3 to 6.7, could not model the batch tests in a satisfactory way. Even by applying a very high reactive surface area (900 m²/g) and imposing an oxygen fugacity at equilibrium with the atmosphere (0.2) for the duration of the simulation, it was not possible to simulate enough U dissolution to fit the experiments.…”
Section: Minerals and Kineticsmentioning
confidence: 99%